The The Effect of the “Siaga” Website on Husband's Behavior in Childbirth Assistance at Afah Fahmi's TPMB Surabaya - Devi Annisa; Evi Pratami; Dina Isfentiani; Kharisma Kusumaningtyas; Mohammed Ismath (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Childbirth is the process of expelling the products of conception (fetus and placenta) that are full-term or nearly full-term and can live outside the womb through the birth canal or without assistance using their own strength. The smooth running of a delivery is influenced by the presence of a companion who is able to provide the support expected by the birthing mother. During this time the husband feels uncomfortable and incompetent to meet the physical or emotional needs of his wife during childbirth. Lack of support and attention by husbands results in many wives experiencing stress during childbirth. The purpose of this study was to analyze the effect of the